2007
DOI: 10.1177/0968051907078611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human apolipoprotein A-I on endotoxin-induced leukocyte adhesion on endothelial cells in vivo and on the growth of Escherichia coli in vitro

Abstract: These data suggest that apo A-I of HDL can directly interact with endotoxin, ameliorating its effect and that apo A-I may have a direct toxic effect on whole bacteria. Therefore, therapeutic use of apo A-I in septicemia and bacterial infection should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…Studies conducted in Oncorhynchus mykiss (Rainbow trout) have confirmed the expression of apoA-I in some of the most important epithelial and mucosal layers [13]. HDL and apoA-I have also been demonstrated to have antimicrobial properties [12,194] inhibiting the growth of Escherichia coli and Staphylococcus epidermidis [173,195], a finding largely attributable to apoA-I. Another innate immune related role of apoA-I which was also discovered in fish is its regulation of the complement system [11].…”
Section: Other Roles In the Innate Immune Response Antiviral Andmentioning
confidence: 82%
See 1 more Smart Citation
“…Studies conducted in Oncorhynchus mykiss (Rainbow trout) have confirmed the expression of apoA-I in some of the most important epithelial and mucosal layers [13]. HDL and apoA-I have also been demonstrated to have antimicrobial properties [12,194] inhibiting the growth of Escherichia coli and Staphylococcus epidermidis [173,195], a finding largely attributable to apoA-I. Another innate immune related role of apoA-I which was also discovered in fish is its regulation of the complement system [11].…”
Section: Other Roles In the Innate Immune Response Antiviral Andmentioning
confidence: 82%
“…In vivo studies conducted in mice and rats have demonstrated that both HDL and apoA-I can reduce leukocyte adhesion and protect against the inflammatory effects of LPS, largely thought to be mediated via the protein component of HDL (i.e., apoA-I) [172][173][174]. A study by Thaveeratitham et al demonstrated that rHDL dose dependently decreases monocyte activation to LPS; however, this was not seen by mature HDL, giving further evidence that apoA-I may be the major protective molecule [173,175].…”
Section: Leukocytesmentioning
confidence: 99%
“…Recently Samanovic et al (4) reported that TLF effectively kills Leishmania promastigotes within the parasitophorous vacuole of macrophages. Additionally, it is known that apoA-1 binds the bacterial outer membrane component lipopolysaccharide (38 -40), protects against the toxic effects of this molecule in vivo (41), and inhibits the growth of Escherichia coli in vitro (42). Thus it is intriguing to consider the possibility that the membrane-destabilizing activity of TLF is also an effective mechanism of combating bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies in both mice and rats have demonstrated that both HDL and apoA-I can reduce leukocyte adhesion and protect the animal from the normal effects of LPS, largely thought to be mediated via the protein component of HDL (i.e. apoA-I) [73][74][75][76]. It was also discovered that patients with low plasma concentrations of HDL are more susceptible to the effects of endotoxin.…”
Section: Leukocytesmentioning
confidence: 99%